KOTA LAYAK ANAK DALAM PERSPEKTIF PERLINDUNGAN ANAK - Irma Rumtianing (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2014)
Child-friendly city is a development system of an administrative area which integrates commitments and resources of the government, society, and business worlds in the fulfillment of children’s rights in a planned, comprehensive and sustainable way. The implementation is done by putting children matters in the first and foremost place. In individual level, this can be done easily. However, it is not that easy in governmental policy level. The awareness of children protection has existed since long time ago. However, when it comes into a state policy, it is only a partial system, not yet a comprehensive one. In Ponorogo children protection program has been implemented. However, there are no a task force of Child-friendly city, no regional action plans, and no local regulation on the protection of women and children. That’s why Ponorogo has not yet got a reward of Childfriendly city. However, the preparation for the reward is getting more mature. Only a few aspects are not ready yet.